An algorithm of dental/dentofacial-based options for managing patients with obstructive sleep apnoea referred to a dentist/dental specialist by a physician - Kılınç, Delal Dara; Didinen, Serhan (Nature Publishing Group, 2016)
There are so many documents in the literature discoursing the aetiology, nature, diagnosis and treatment planning of obstructive sleep apnoea (OSA). Almost all of them mention that OSA has to be evaluated and treated through the multidisciplinary teamwork of physicians and dentists. Due to a lack in the literature, this article focuses on dentists' and dental specialists' role in the treatment algorithm of OSA.
Medical Technologies National Conference, TIPTEKNO 2015 -- 15 October 2015 through 18 October 2015 -- 118954
Keywords: Sleep Apnea, Obstructive; Mandibular Advancement; Oral Appliances